2020
DOI: 10.1083/jcb.201910215
|View full text |Cite
|
Sign up to set email alerts
|

The LTB4–BLT1 axis regulates actomyosin and β2-integrin dynamics during neutrophil extravasation

Abstract: The eicosanoid leukotriene B4 (LTB4) relays chemotactic signals to direct neutrophil migration to inflamed sites through its receptor BLT1. However, the mechanisms by which the LTB4–BLT1 axis relays chemotactic signals during intravascular neutrophil response to inflammation remain unclear. Here, we report that LTB4 produced by neutrophils acts as an autocrine/paracrine signal to direct the vascular recruitment, arrest, and extravasation of neutrophils in a sterile inflammation model in the mouse footpad. Usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Interestingly, the packaging of LTB 4 in small EVs has been observed in macrophages and dendritic cells, where the vesicles were shown to promote migration (Esser et al, 2010). EV secretion and LTB 4 signaling are also required for neutrophil arrest and extravasation in a sterile mouse footpad model of inflammation (Subramanian et al, 2020). In this context, it is envisioned that LTB 4 -containing exosomes act to propagate chemotactic signals between cells by protecting LTB 4 from degradation in harsh extracellular environments.…”
Section: Evs In Immune Cell Chemotaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the packaging of LTB 4 in small EVs has been observed in macrophages and dendritic cells, where the vesicles were shown to promote migration (Esser et al, 2010). EV secretion and LTB 4 signaling are also required for neutrophil arrest and extravasation in a sterile mouse footpad model of inflammation (Subramanian et al, 2020). In this context, it is envisioned that LTB 4 -containing exosomes act to propagate chemotactic signals between cells by protecting LTB 4 from degradation in harsh extracellular environments.…”
Section: Evs In Immune Cell Chemotaxismentioning
confidence: 99%
“…Attachment of exosomes to the ECM in tissues may also allow maintenance of secondary gradients. Thus, exosomes from cancer cells have been observed attached to collagen fibers in vivo (Sung et al, 2020), and integrin-containing EVs are released from neutrophils in vivo during extravasation (Subramanian et al, 2020). Furthermore, EVs from stimulated neutrophils use integrin signaling to anchor to the ECM (Genschmer et al, 2019).…”
Section: Evs In Immune Cell Chemotaxismentioning
confidence: 99%
“…Obviously, exosomes can serve as chemoattractant signals for the extravasation of neutrophils into inflamed tissues. Subramanian et al found that the exosomes shed from neutrophils adhere to the endothelium in an integrin β2-dependent manner and locally release leukotriene B4 (LTB4), which is critical for neutrophil recruitment and extravasation in response to inflammatory signals [ 105 ]. The potential role of activated neutrophil exosomes in pulmonary diseases, such as chronic obstructive pulmonary disease and bronchopulmonary dysplasia, is also noted.…”
Section: Integrin Regulation In Exosomesmentioning
confidence: 99%
“…In recent years, in vivo imaging has revealed that, in a variety of physiological and pathological contexts, cells undergo large deformations 1 , sometimes being squeezed to a tenth of their resting diameter. Migrating cells, in particular fast-moving immune or cancer cells, can deform to a large extent in only a few minutes [2][3][4] , for example when they cross an endothelial barrier 5 . Even faster deformations, below the second timescale, can be observed in circulating cells pushed through small blood capillaries.…”
Section: Introductionmentioning
confidence: 99%